One pot synthesis of tetrasubstituted thiophenes: [3 + 2] annulation strategy1. Issue 46 (23rd May 2015) - Sahu, Satya Narayan; Gupta, Maneesh Kumar; Singh, Surjeet; Yadav, Pratik; Panwar, Rahul; Kumar, Abhinav; Ram, Vishnu Ji; Kumar, Brijesh; Pratap, Ramendra
<x xml:space="preserve">Abstract</x> A simple, efficient and economical synthesis of dimethyl 3-amino-5-(2-oxo-2-arylethyl)thiophene-2, 4-dicarboxylates has been reported by ring opening of methyl 3-amino-6-aryl-4-oxo-4H-thieno[3, 2-c]pyran-2-carboxylates by alkoxide ions.